A Comparative Morphometric Analysis of Three Cranial Nerves in Two Phocids: The Hooded Seal (Cystophora cristata) and the Harbor Seal (Phoca vitulina). Issue 3 (21st December 2015) - Wohlert, Dennis; Kröger, Jürgen; Witt, Martin; Schmitt, Oliver; Wree, Andreas; Czech‐Damal, Nicole; Siebert, Ursula; Folkow, Lars; Hanke, Frederike D.
ABSTRACT: While our knowledge about the senses of pinnipeds has increased over the last decades almost nothing is known about the organization of the neuroanatomical pathways. In a first approach to this field of research, we assessed the total number of myelinated axons of three cranial nerves (CNs) in the harbor (Phoca vitulina, Pv) and hooded seal (Cystophora cristata, Cc) . Axons were counted in semithin sections of the nerves embedded in Epon and stained with toluidine blue. In both species, the highest axon number was found within the optic nerve ( Pv 187, 000 ± 8, 000 axons, Cc 481, 600 ± 1, 300 axons). Generally, considering absolute axon numbers, far more axons were counted within the optic and trigmenial nerve ( Pv 136, 700 ± 2, 500 axons, Cc 179, 300 ± 6, 900 axons) in hooded in comparison to harbor seals. The axon counts of the vestibulocochlear nerve are nearly identical for both species ( Pv 87, 100 ± 8, 100 axons, Cc 86, 600 ± 2, 700 axons). However, when comparing cell density, the cell density is almost equal for all nerves for both species except for the optic nerve in which cell density was particularly higher than in the other nerves and higher in hooded in comparison to harbor seals. We here present the first comparative analysis of three CNs in two phocid seals. While the CNs of these closely related species share some general characteristics, pronounced differences in axon numbers/densities are apparent. These differences seem to reflect differences in e.g. size, habitat, and/or functional significance of the innervated sensory systems. Anat Rec, 299:370–378, 2016. © 2015 Wiley Periodicals, Inc.